2016
DOI: 10.1007/s00705-016-3148-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular characterization of a novel sugarcane streak mastrevirus and an isolate of the A-strain of maize streak virus from sugarcane in Nigeria

Abstract: Sugarcane and maize plants showing symptoms typical of those described for the so-called "African streak viruses" (AfSVs) were encountered during field surveys conducted from February to July 2015 to document viruses infecting both crops across the northern Guinea savannah region of Nigeria. As part of this study, two categories of complete mastrevirus-like genome sequences were obtained from nine samples (maize = 2; sugarcane = 7). In pairwise comparisons, the full-length genomes of the first sequence categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
0
4
2
Order By: Relevance
“…ESV and USV are the closest mastreviruses to SCSV with 75-76% full genome identity, which is below the 78% demarcation threshold for Mastrevirus species. For undetermined reasons, these values for ESV and USV identity with SCSV are higher in our study as compared to the ones reported previously [4]. Furthermore, no signi cant recombination event was found in the SCSV genome of 17 isolates using RPD5 program, which differs also with the previous report on SCSV in Nigeria that described occurrence of one recombination in the CP gene [4].…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…ESV and USV are the closest mastreviruses to SCSV with 75-76% full genome identity, which is below the 78% demarcation threshold for Mastrevirus species. For undetermined reasons, these values for ESV and USV identity with SCSV are higher in our study as compared to the ones reported previously [4]. Furthermore, no signi cant recombination event was found in the SCSV genome of 17 isolates using RPD5 program, which differs also with the previous report on SCSV in Nigeria that described occurrence of one recombination in the CP gene [4].…”
Section: Discussioncontrasting
confidence: 93%
“…If the presence of SCMV (one of the causal agents of mosaic disease with SrMV) was well known for several decades [13], this is to our knowledge the rst report of SCSV in Cameroon. The only other sugarcane growing location where this virus has been found so far is Nigeria, a border country of Cameroon [4]. The prevalence of SCSV in sugarcane commercial elds and the impact of this virus on crop yields are currently unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[50] used agroinfection to rapidly screen for MSV resistance in various maize genotypes. MSV can be detected using ELISA test kits and PCR [52,53]. A PCR-RFLP technique is being employed in differentiating the strains of MSV [54].…”
Section: Maize Streak Virus (Msv)mentioning
confidence: 99%